Pengaruh ROE dan DER terhadap Harga Saham melalui EPS sebagai Variabel Intervening Pada Sektor Energi yang Terdaftar di BEI 2020-2024 - Rina Sulistia Ningrum (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to determine the effect of ROE and DER on Stock Price with EPS as an intervening variable in the energy sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The population in this study uses the energy sector listed on the Indonesia Stock Exchange for the period 2020-2024 using the Purpose Sampling method. The analysis method in this study is multiple linear regression analysis. The results of this study determine that ROE partially affects EPS. DER partially has a negative effect on EPS. ROE and DER have a combined effect on EPS. ROE partially affects Stock Price. DER partially does not affect Stock Price. EPS partially affects Stock Price. ROE, DER, and EPS have a combined effect on Stock Price. Earnings Per Share can mediate the effect of ROE on Stock Price. Earnings Per Share cannot mediate the effect of DER on Stock Price in the energy sector listed on the Indonesia Stock Exchange for the period 2020-2024.